Analysis of Social Meaning in “I Have a Dream” Speech - Hutri Budiman; Ismail (PRAGMATICA : Journal of Linguistics and Literature, 2025)
This study analyzed social meaning in Martin Luther King Jr.’s “I Have a Dream” speech, a pivotal civil rights text, to understand its reflection of 1963 America’s socio-cultural context. Despite extensive studies on the speech’s structure and emotional impact, none have applied Leech’s social meaning framework. This research aims to identify sentences conveying social meaning and analyze their linguistic construction using Leech’s theory. A qualitative close reading method was employed, selecting 17 sentences from the official transcript. Findings reveal metaphors like “bad check” and “bank of justice” that critique systemic racism, while phrases like “together” and “faith” foster interracial unity. These reflect voting barriers, segregation, and moral contradictions in America’s democratic ideals. The study advances semantics by applying Leech’s framework to historical discourse, offering insights for linguistic and civil rights scholarship. It underscores language’s role in advocating justice and inspiring change.